Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT Kamadjaja Logistics Medan - Muhammad Dafa Maulana; Yahya Tanjung (Economic Reviews Journal, 2024)
A person's leadership style in leading is very influential and is a determining factor in increasing and decreasing employee performance. Therefore, it is clear that every company needs a leader who is able to work together with its employees. Then, the second problem is the less conducive working environment. The work environment is the material and psychological conditions that exist in the organization, the company must provide an adequate work environment. The aim of this research is to determine the influence of leadership style and work environment on employee performance at PT. Kamadjaja Logistics Medan.The method in this research is quantitative. The population in the study were employees at PT. Kamadjaja Logistics Medan, totaling 83 employees. The data sources in this research are primary and secondary data. Meanwhile, the data analysis technique used is multiple linear regression analysis.Test results (t) or partial test on the Leadership Style variable (X1) on Employee Performance (Y), Sig value. 0.000 < significance level α = 5%. This means that the Leadership Style variable has a significant influence on the Employee Performance variable. Apart from that, the influence of the Work Environment variable (X2) on Employee Performance (Y) has a value of Sig. 0.000 < significance level α = 5%. This means that the Work Environment variable has a significant influence on the Employee Performance variable.